Riview Artikel : Representasi Tabel Dalam Pemahaman Matematika Sebagai Sarana Berfikir Deduktif Terhadap Mahasiswa Pendidikan Fisika - Liana Shafa K; Mellya Syafiratul H; Sintia Lestari; Ernasari Ernasari; Sri Handono (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This article discusses mathematical thinking in a deductive way. Mathematics is a branch of science that deals with abstract forms or structures. Deductive thinking is the process of drawing conclusions based on premises whose existence has been determined. The purpose of this research is to determine whether the use or application of tables can facilitate general understanding of mathematics for physics education students. The method used in this research is a systematic, explicit and reproducible review of articles to identify, evaluate and synthesize research works and thoughts that have been produced in related journals. The results of this research show that tabular representation in understanding mathematics as a means of descriptive thinking for physics education students greatly facilitates solving physics problems. The conclusion from this research is that the application of mathematics as deductive thinking greatly facilitates solving problems in mathematics or physics.